Proteomics Variation in Nigella Sativa L. (Rananculaceae) Germplasm (Bangladesh Journal of Botany, 2021)
Study revealed a first report of proteomics variation in Nigella sativa L. based on analyzing 32 accessions through SDS-PAGE. Three prominent regions along eight subunits were identified. Intra specific variation was observed low whereas the sharpness of bands was high between first and second regions. It was noted that in second region there was no clear evidence of band formation in N. sativa. Prominent and sharp protein peptide bands were recorded in four accessions, namely PK-020561, PK-020609, PK-020620 and PK-020646. Further investigation of single seeds showed almost similar genetic pattern within the single accession. Five clusters were formed on the basis of Euclidean distance. Cluster-I & II contain 1, 1 accession each, likewise Cluster-III and C-IV contain 2, 2 accessions whereas Cluster-V was found diversified as consisted of 26 accessions. Two accessions PK-020878 and PK-020877 were recommended for polymorphism and crop improvement programs.Bangladesh J. Bot. 50(2): 289-294, 2021 (June)